2006
DOI: 10.1097/01.meg.0000228976.64774.04
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproliferative small intestinal disease in Greece: presentation of 13 cases including two from Albania

Abstract: The patients were categorized in three subgroups of IPSID: alpha-chain disease (n=8), non-alpha chain disease with other monoclonal immunoglobulins (n=3), and polyclonal 'non-malignant' IPSID (n=2). In several patients the disease had unusual features, and this in some cases delayed the diagnosis. In suspected cases it is thus of the utmost importance to proceed to an exploratory laparatomy. Patients with stage C disease had a short survival, whereas two patients with stage A alpha-chain disease responded to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…However, initially benign-appearing lesions often evolve into aggressive high-grade lymphomas (as in our case), invading the intestinal wall and mesenteric lymph nodes, and they may also metastasize to distant organs. 3,4 In half of the cases, the initially diagnosed IPSID coexists with a high-grade B-cell lymphoma. 1 The fi rst-line therapy of the advanced stage of IPSID is rituximab (a chimeric monoclonal antibody directed against the CD20 antigen), which, in combination with conventional chemotherapy, has been associated with higher response rates, a longer event-free survival, and a longer overall survival, over combination chemotherapy alone.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, initially benign-appearing lesions often evolve into aggressive high-grade lymphomas (as in our case), invading the intestinal wall and mesenteric lymph nodes, and they may also metastasize to distant organs. 3,4 In half of the cases, the initially diagnosed IPSID coexists with a high-grade B-cell lymphoma. 1 The fi rst-line therapy of the advanced stage of IPSID is rituximab (a chimeric monoclonal antibody directed against the CD20 antigen), which, in combination with conventional chemotherapy, has been associated with higher response rates, a longer event-free survival, and a longer overall survival, over combination chemotherapy alone.…”
Section: Discussionmentioning
confidence: 98%
“…Molecular and immunohistochemical studies have demonstrated an association with Helicobacter pylori and Campylobacter jejuni. 3,4 The symptoms include diarrhea, abdominal pain, weight loss, and occasionally fever and lymphadenopathy. 3,4 A staging system for IPSID has emerged as a reliable prognostic and therapeutic parameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IPSID has had many synonyms due to its broad symptomatic spectrum. In the early 1960s, young adults from Israel were reported to present small intestinal lymphoma associated with malabsorption symptoms, coining the term Mediterranean Lymphoma to this disease, as it was predominantly found in patients from that geographical region [1,2]. In 1965, Bracha was the first to describe 13 patients in Tel-Hashomer hospital with this syndrome [3,4].…”
Section: Introductionmentioning
confidence: 99%